2019
DOI: 10.1063/1.5079703
|View full text |Cite
|
Sign up to set email alerts
|

Transition of predominant mechanism for the deviation of micro-gap dc gas breakdown character with electrode gap changing

Abstract: This paper explores the predominant mechanisms for the deviation of micro-gap dc gas breakdown and the transition between different mechanisms as the electrode separation d changing under a pin-to-plate electrode configuration using 2d3v particle-in-cell simulation with Monte Carlo collisions. The deviated breakdown characteristic curves as a function of d or gas pressure p are investigated and both present a plateau region. Through researching the position of discharge path, it is found that a self-modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Resulting in the product of gas pressure and the discharge path length(ps) approximates the pd value associated with the minimum breakdown voltage, thus sustaining the minimum breakdown voltage [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Resulting in the product of gas pressure and the discharge path length(ps) approximates the pd value associated with the minimum breakdown voltage, thus sustaining the minimum breakdown voltage [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, microscale geometries present a challenge to the traditional understanding of the electrical breakdown of a gas gap that has described and predicted for over a century by Paschen's law [6], which shows that the breakdown voltage V br as a function of the product of gas pressure p and gap distance d (also known as a Paschen curve) has a decreasing left branch and an increasing right branch. In the case of micro-gap discharge, the gas breakdown features deviate significantly from the classical Paschen's law when the dimensions are in the range of 1-10 µm [1] due to the distribution of an ion-enhanced field emission effect [7] or the self-modulation effect [8]. This paper focuses on microcavity discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In a small air gap, the self-modulation effect of the electron makes the discharge path longer [11], making the PD value approximately equal to the Pd value corresponding to the minimum breakdown voltage, that is, PD ≈ (Pd) min (D is the actual breakdown path distance). By establishing a DCP model of two non-parallel straight plate electrodes, Yu Bo and other scholars found that when the pressure changes, the initial path of breakdown will shift [12], and the entire electrode channel will always choose the path most likely to cause breakdown under different working conditions. At present, based on the breakdown characteristics of the at electrode with micron spacing and the appearance of the breakdown voltage "plateau period", Paschen curve is no longer fully applicable to the breakdown characteristics of the at electrode.…”
Section: Introductionmentioning
confidence: 99%